Samsung Galaxy Tabs For Dummies - Gookin, Dan (Hoboken, New Jersey John Wiley & Sons, Inc., 2014)
A colorful, entertaining, and informative guide to the Samsung Galaxy family of tablets Samsung's bestselling Galaxy Tabs may come in multiple sizes, but they all share the wildly popular Android operating system and are packed with tons of top-notch tablet features.
Includes Index and Illustrations.
Keywords: Samsung Galaxy Tab (Ordinateur)